Pengaruh Pemberian Media Kartu Suku Kata Terhadap Kemampuan Kualitas Membaca pada Siswa - Tanjung, Cici Febi Putri; Anas, Nirwana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Syllable card media is a tool aimed at enhancing students' early reading skills by visualizing images and syllables that are affixed to a board. The purpose of this study is to investigate the Influence of Syllable Card Media on Reading Ability Quality of Students. The research was conducted at a public elementary school in Deli Serdang, with the subjects being second semester first-grade students, consisting of two classes: class IA and 1B. The research utilized a quantitative method with a Quasi-Experimental approach. The results from the Wilcoxon signed-rank test indicated an Asymp. Sig (2-tailed) value of 0.000, which is smaller than 0.05 (0.000 < 0.05). This leads to the conclusion that the "Hypothesis is Accepted," implying a difference in students' early reading ability using media between the Pre-Test and Post-Test. Thus, it is evident that Syllable Card Media has an Influence on the Quality of Reading Ability among Students. The recommendation from this research is for educators to utilize media in teaching to enhance early reading skills.